Faktor Faktor Yang Berhubungan Dengan Minat Penggunaan Iud Pada Ibu Hamil Trimester III Di Poliklinik Rsud Banyumas - Meilyn Amina Faurur; Purwati (NERSMID : Jurnal Keperawatan dan Kebidanan, 2026)
Indonesia faces the challenge of rapid population growth. The national family planning program, particularly the use of intrauterine devices (IUDs) as a long-term contraceptive method, is a key strategy to address this issue. However, the uptake of long-term contraceptive methods (Metode Kontrasepsi Jangka Panjang/MKJP) at RSUD (Regional Public Hospital) Banyumas remains low. This study aims to analyze the factors associated with third-trimester pregnant womens interest in using IUDs. This research employed a cross-sectional analytic correlational design involving 93 respondents. Data analysis was conducted using the Spearman Rank correlation test to examine relationships between the dependent variable (interest in using IUDs) and the independent variables: parity, knowledge level, income, husbands support, and education. Results there was no statistically significant association between education level (p = 0.359) or parity (p = 0.487) and interest in IUD use. However, significant associations were found between income (p = 0.044), knowledge (p = 0.031), and husbands support (p = 0.001) and the interest in using IUDs. Conclusion the majority of respondents had a high level of education, income below the regional minimum wage, were multiparous, possessed moderate knowledge, and reported strong support from their husbands. Husbands support was found to have a moderately strong influence on interest in IUD use. It is recommended that health workers enhance educational efforts and actively involve husbands in the counseling process. RSUD Banyumas is also encouraged to develop Information, Education, and Communication (IEC/KIE) programs targeted at couples. Future research should consider exploring other influencing factors such as perceived side effects, cultural and religious beliefs, and counseling history.